C-reactive protein, procalcitonin, D-dimer, and ferritin in severe coronavirus disease-2019: a meta-analysis. (June 2020) - Huang, Ian; Pranata, Raymond; Lim, Michael Anthonius; Oehadian, Amaylia; Alisjahbana, Bachti
Background: Patients critically ill with coronavirus disease-2019 (COVID-19) feature hyperinflammation, and the associated biomarkers may be beneficial for risk stratification. We aimed to investigate the association between several biomarkers, including serum C-reactive protein (CRP), procalcitonin (PCT), D-dimer, and serum ferritin, and COVID-19 severity. Methods: We performed a comprehensive systematic literature search through electronic databases. The outcome of interest for this study was the composite poor outcome, which comprises mortality, acute respiratory distress syndrome, need for care in an intensive care unit, and severe COVID-19. Results: A total of 5350 patients were pooled from 25 studies. Elevated CRP was associated with an increased composite poor outcome [risk ratio (RR) 1.84 (1.45, 2.33), p < 0.001; I 2 : 96%] and its severe COVID-19 (RR 1.41; I 2 : 93%) subgroup. A CRP ⩾10 mg/L has a 51% sensitivity, 88% specificity, likelihood ratio (LR) + of 4.1, LR- of 0.5, and an area under curve (AUC) of 0.84. An elevated PCT was associated with an increased composite poor outcome [RR 3.92 (2.42, 6.35), p < 0.001; I 2 : 85%] and its mortality (RR 6.26; I 2 : 96%) and severe COVID-19 (RR 3.93; I 2 : 63%) subgroups. A PCT ⩾0.5 ng/ml has an 88% sensitivity, 68% specificity, LR+ of 2.7, LR- of 0.2, and an AUC of 0.88. An elevated D-dimer was associated with an increased composite poor outcome [RR 2.93 (2.14, 4.01), p < 0.001; I 2 : 77%], including its mortality (RR 4.15; I 2 : 83%) and severe COVID-19 (RR 2.42; I 2 : 58%) subgroups. A D-dimer >0.5 mg/L has a 58% sensitivity, 69% specificity, LR+ of 1.8, LR- of 0.6, and an AUC of 0.69. Patients with a composite poor outcome had a higher serum ferritin with a standardized mean difference of 0.90 (0.64, 1.15), p < 0.0001; I 2 : 76%. Conclusion: This meta-analysis showed that an elevated serum CRP, PCT, D-dimer, and ferritin were associated with a poor outcome in COVID-19. The reviews of this paper are available via the supplemental material section.